2000
DOI: 10.17016/bulletin.2000.86-9
|View full text |Cite
|
Sign up to set email alerts
|

Credit Cards: Use and Consumer Attitudes, 1970-2000

Abstract: From modest origins in the l950s as a convenient way for the relatively well-to-do to settle restaurant and department store purchases without carrying cash, credit cards have become a ubiquitous financial product held by households in all economic strata. Since the late 1960s, much federal legislation has been enacted to ensure that consumers have the protections and information they need to use this widely available form of open-end credit wisely. Nevertheless, concerns persist about whether consumers fully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 1 publication
1
42
0
Order By: Relevance
“…Credit cards serve as both a payment means and a short-term financing instrument. The popularity of credit cards as a payment means has been attributed mainly to convenience (e.g., Durkin, 2000), to less-time-consuming shopping services (Kinsey, 1981), to their necessity for Internet transactions, and to add-on offerings, such as frequent-use awards, flight miles, and other benefits. Credit cards are also used as a medium for revolving consumer credit, which allows people to borrow within their credit limit without transaction costs.…”
Section: Behavior In Credit Marketsmentioning
confidence: 99%
See 3 more Smart Citations
“…Credit cards serve as both a payment means and a short-term financing instrument. The popularity of credit cards as a payment means has been attributed mainly to convenience (e.g., Durkin, 2000), to less-time-consuming shopping services (Kinsey, 1981), to their necessity for Internet transactions, and to add-on offerings, such as frequent-use awards, flight miles, and other benefits. Credit cards are also used as a medium for revolving consumer credit, which allows people to borrow within their credit limit without transaction costs.…”
Section: Behavior In Credit Marketsmentioning
confidence: 99%
“…At the beginning of the 1990s, approximately 20% of credit users indicated that they had considered searching (Chang & Hanna, 1992), whereas in 2003 only one third of people holding a credit card had compared various offers before application (Hilgert, Hogarth, & Beverly, 2003). Credit card users believe that it is easy to obtain information and so, ironically, they do not seem to think it is necessary to do so (Durkin, 2000). An individual’s house bank (i.e., holding his or her savings account, salary account, etc.)…”
Section: Behavior In Credit Marketsmentioning
confidence: 99%
See 2 more Smart Citations
“…Even under the new rules the personal-bankruptcy rate has increased steadily, hitting 1.2 per 1,000 people by the second quarter of 2009, after a year and a half of recession. 2 Numerous explanations for this rise have been offered and estimated empirically: the increased use of credit cards and increased consumer debt [Durkin (2000); White (2007)], the spread of casino gambling [Barron et al (2002); Thalheimer and Ali (2004); Garrett and Nichols (2008)], a reduced social stigma associated with filing for bankruptcy [Garrett (2007)], changes to state and federal bankruptcy laws [Nelson (1999)], and greater access to secured and unsecured credit [Gropp et al (1997)]. 3 Most recently, Livshits et al (2010) modeled and compared the various explanations and concluded that "a decrease in the transactions cost of lending and in the cost of bankruptcy" account for the rise in personal bankruptcy.…”
Section: The Personal-bankruptcy Literaturementioning
confidence: 99%